Pengaruh Aplikasi Solid Decanter dan Biochar terhadap Kadar Hara dalam Air Lindi Tanah Pascatambang Batu Bara - Christiani, Dwi; Hartati, Wahyuni; Syahrinudin, Syahrinudin (IAI Nasional Laa Roiba Bogor, 2024)
Open pit coal mining activities affect the decline in soil quality characterized by damage of soil structure, loss of nutrients and decreased biodiversity. Organic matter is one of the soil reformers that has been felt its benefits in improving soil properties both physical, chemical, and bi ological properties. This study aims to determine the effect of solid and biochar administration on post coal mining soil on water storage capacity and giraffe power on nutrients in percolation water administration. This research was carried out at the Laboratory of Soil Science and Forest Nutrition, Mulawarman Samarinda University, East Kalimantan following the rules of Factorial Complete Random Design with two factors, namely solid percentage and biochar with percolation water treatment during the one month incubation period. The results showed the application of S2B2 (solid 20% + biochar 25%) was able to have an influence on water giraffe power with a three day incubation period end value of 92.2 ml, fifteen days of 89.3 ml and thirty days of 85.6 ml. The application of biochar 5% and 25% in post coal mine soils of fifteen days and thirty days incubation period shows the ability to absorb calcium nutrient levels in leachate water. The combined application of S2B2 (solid 20% + biochar 25%) showed a good ability to absorb calcium and magnesium nutrient levels in leachate water that decreased during the incubation period.